2012
DOI: 10.1111/gbb.12005
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical coherent‐gene‐group model for brain development

Abstract: We have described a strategy to analyze the data available on brain genes expression, using the concept of coherent-gene groups controlled by transcription factors (TFs). A hierarchical model of gene-expression patterns during brain development was established that identified the genes assumed to behave as functionally coding.Analysis of the concerned signaling pathways and processes showed distinct temporal gene-expression patterns in relation with neurogenesis/synaptogenesis. We identified the hierarchical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 105 publications
3
22
0
Order By: Relevance
“…If replicated, the identified TF motifs associated with DEGs in mood disorder diagnoses and overall disease morbidity will likely reveal a vulnerability in the general transcriptional pathway mechanism in mood disorder disease states.The identified DEG-profile associated TF motifs are known to regulate expression of tolllike receptor signaling genes, cellular homeostatic control genes, and embryonic and cellular including neurodevelopmental gene networks found to be differentially expressed in BD vs. controls, MDD vs. controls, and in high Axis-I comorbid mood disorder individuals vs. low Axis-I comorbidity mood disorder individuals. We found putative hierarchical TF regulatory involvement in the gene expression landscapes associated with BD and MDD diagnoses, such that enrichments of master transcription factors were predominantly associated with the gene expression landscape in elevated mood disorder morbidity, thereby echoing previous work(Tsigelny et al 2013; Lee & Young 2013; Changeaux 2017;Lambert et al 2018; Chen C et al 2019). It is important to note that a number of the TFs we have associated with anterior insula gene expression in bipolar disorder vs. controls (i.e., MIB2, Esrrb, MZF1, and ZNF148) and in major depressives vs. controls (i.e., PCP1, HNF1B, and Esrrb) are novel in that they have not been previously been identified in any genetic screens.…”
supporting
confidence: 85%
“…If replicated, the identified TF motifs associated with DEGs in mood disorder diagnoses and overall disease morbidity will likely reveal a vulnerability in the general transcriptional pathway mechanism in mood disorder disease states.The identified DEG-profile associated TF motifs are known to regulate expression of tolllike receptor signaling genes, cellular homeostatic control genes, and embryonic and cellular including neurodevelopmental gene networks found to be differentially expressed in BD vs. controls, MDD vs. controls, and in high Axis-I comorbid mood disorder individuals vs. low Axis-I comorbidity mood disorder individuals. We found putative hierarchical TF regulatory involvement in the gene expression landscapes associated with BD and MDD diagnoses, such that enrichments of master transcription factors were predominantly associated with the gene expression landscape in elevated mood disorder morbidity, thereby echoing previous work(Tsigelny et al 2013; Lee & Young 2013; Changeaux 2017;Lambert et al 2018; Chen C et al 2019). It is important to note that a number of the TFs we have associated with anterior insula gene expression in bipolar disorder vs. controls (i.e., MIB2, Esrrb, MZF1, and ZNF148) and in major depressives vs. controls (i.e., PCP1, HNF1B, and Esrrb) are novel in that they have not been previously been identified in any genetic screens.…”
supporting
confidence: 85%
“…Post mortem studies have indicated that ASD patients display pathologic neuroanatomical changes pointing to defects in neurogenesis (Wegiel et al, 2010). Moreover, genetic studies conducted on human tissue have highlighted the role of neurogenesis as a key biological process involved in ASD pathophysiology (Hussman et al, 2011;Kumar et al, 2011;Tsigelny, Kouznetsova, Baitaluk, & Changeux, 2013). In that context, BTBR mice provide a useful model as recent studies describe extensive neuroanatomical differences from C57BL/6 mice (a commonly used control strain) (Ellegood, Babineau, Henkelman, Lerch, & Crawley, 2013) and alterations in connective tissue/vasculature and associated extracellular matrix in a neurogenic niche of these mice (Mercier, Cho Kwon, & Kodama, 2011), alongside with histopathological findings indicating reduced hippocampal neurogenesis (Stephenson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies in neuroeconomics and neurofinance [3,14] should examine neural basis of this psychological tendency. Furthermore, recent advances in high throughput genomic data in neurobiology by Changeux's group can help us to analyze brain's organization by utilizing Tsallis' statistics [19]. Future neuroeconomic studies can also utilize this type of research strategies by utilizing q-generalized statistics.…”
Section: Discussionmentioning
confidence: 99%